METAFORA GANDA PADA KATA MAJEMUK 935 BAHASA INGGRIS - Teddy Yusuf (JURNAL ISTEK, 2014)
The research on lexeme configurations of English compound in Indonesia has not touched the aspect of figurative language. Therefore, this research has done to fill the gap. Based on the research problem, this research is aimed to study and to describe the figurative language in the lexemes of compound word of English language on the view of: (1) the structure pattern of Adjective + Noun in compound Word (2) the structure pattern of Noun + Noun in compound word, (3) the structure pattern of Noun + Adjective in compound word, (4) the figurative language on modifier lexemes in compound word, (5) the figurative language on lexemes of the head unit in compound word, (6) the figurative language on lexemes both modifier and the head unit in compound word. The theories applied in this research is eclectic. Structural morphology theory used to study the form of structure in compound word. Cognitive semantic theory used to study the lexemes from the aspect of figurative language in modifier unit, in the head unit of compound word, or in both (modifier unit and the head unit of compound word) as the compound word which convey the idiomatic meaning. The research method used in this research is descriptive. The method of study applied is distribution method, substitution, extension and insertion as a base to differentiate between a compound word from noun phrase. The results of research show that compound word in English (1) have the structure pattern as Adjective + Noun, Noun + Noun and Noun + Adjective, (2) compound word in English with figurative language on lexeme of modifier have formula N2 = N1 or N2 is N1 metaphorically, (3) compound word in English with figurative language on lexeme of head unit have the formula as follow; N1 is ' navigation' lexeme that becomes a base of changing in a referent (literal meaning) in those compound words or N1 is a 'navigation' lexeme that becomes a base in creating the form of metaphor which is intended in N2 so that results in the figurative language, (4) compound word in English with lexeme of figurative language in modifier unit or in the head unit will results in the change of meaning, that is a transfer of meaning from literal meaning towards idiomatic meaning. The creation of idiomatic meaning stands from the root of metaphor which represented in each lexemes in the compound words as their constituent.